Analisis Ekonomi Islam pada Program Jaminan Sosial Ketenagakerjaan Konsumen Bukan Penerima Upah di BPJS Ketenagakerjaan Cabang Pinrang - Sri Wahyuni; Desy Arum Sunarta; Mustamin B (STAI DDI Pinrang, 2025)
Indonesia with a Muslim majority does not necessarily know the Islamic economy in the Employment Social Security program at BPJS Ketenagakerjaan. So it is necessary to analyze the Social Security program to find out the application of Islamic economics, especially the segmentation of Non-Wage Earners This study aims to determine the form of the employment social security program and to find out the Islamic economy on the Non-Wage Recipient consumer employment social security program. This type of research is descriptive qualitative research where researchers go into the field to explore information on employees and consumers who are not wage earners. The results of this study are. (1) There are 3 forms of employment social security programs for consumers who are not wage earners, namely: Work Accident Insurance, Death Insurance and Old Age Insurance. (2) Islamic economic analysis on the employment social security program for Non-Wage Receiving consumers at BPJS Ketenagakerjaan Pinrang has been based on the principles of Islamic economics where 5 principles are the principles of tawhid, justice, responsibility, truth and honesty, and the principle of willingness.